zad 4 ................
![Zad 4 class=](https://pl-static.z-dn.net/files/d3c/d1f3a83d0d6aec5702e8e9796f5c3974.png)
Odpowiedź:
[tex]a)\ \ (\sqrt{5}x+2)^2=(\sqrt{5}x)^2+2\cdot\sqrt{5}x\cdot2+2^2=5x^2+4\sqrt{5}x+4\\\\b)\ \ (2x-\frac{1}{3})^2=(2x)^2-2\cdot2x\cdot\frac{1}{3}+(\frac{1}{3})^2=4x^2-\frac{4}{3}x+\frac{1}{9}\\\\c)\ \ (\sqrt{7}x-0,3)(\sqrt{7}x+0,3)=(\sqrt{7}x)^2-0,3^2=7x^2-0,09[/tex]
Szczegółowe wyjaśnienie:
[tex]Zastosowane\ \ wzory\\\\(a+b)^2=a^2+2ab+b^2\\\\(a-b)^2=a^2-2ab+b^2\\\\((a-b)(a+b)=a^2-b^2[/tex]